1974
DOI: 10.1103/physrevc.9.2067
|View full text |Cite
|
Sign up to set email alerts
|

Masses forAr43and the new isotopesAr

Abstract: The reactions (n,~Be), (n, Be), and (Li, SB) on +Ca at E(n)=78 MeV and E( Li)=80 MeV were used to determine the mass excesses of 3Ar (-31. 98+ 0.07 MeV}, 4~Ar(-29.727 + 0.06 MeV}, and 48Ar (-29.732+ 0.07 MeV} by counter telescope techniques. Excited states in 4~Ar at 1.74+0.05, 2.55+0.05, 3.56+0.07, and 4.74+0.10 MeV and in 45Ar at 1.66+0.05, 2.42+0.05, and 3.25+ 0.07 MeV were also observed. Comparisons are made with mass predictions calculated from simple mass relations based on the shell model and with those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

1977
1977
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 7 publications
3
9
0
Order By: Relevance
“…The mass measurement of 41 Si [216] corresponds to a negative one-neutron separation energy of −20 ± 1930 keV [105]. Although this value is consistent with the observation that 41 Si is bound [200], one would expect 43 Si to be unbound (−190 ± 860 keV, [105]). However, 43 Si is also bound [214].…”
Section: Isotones With N > 20supporting
confidence: 79%
See 2 more Smart Citations
“…The mass measurement of 41 Si [216] corresponds to a negative one-neutron separation energy of −20 ± 1930 keV [105]. Although this value is consistent with the observation that 41 Si is bound [200], one would expect 43 Si to be unbound (−190 ± 860 keV, [105]). However, 43 Si is also bound [214].…”
Section: Isotones With N > 20supporting
confidence: 79%
“…The use of more complicated multiparticle transfer reactions lead to the first observation of the proton dripline nuclei 9 C, 20 Mg, and 22 Al by means of the reactions 12 C( 3 He, 6 He) 9 43 Cl [44].…”
Section: Transfer Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier mass measurements for neutron rich nuclei with light ion induced reactions (see for example Refs. 8,17) as well as the (1sO, ZONe) reaction using counter telescopes, have led to possible errors of typically > 50 keV dominated essentially by relatively poor statistics. We have shown that by profiting from the large (lsO, 2~ cross sections at small angles, one obtains precise mass values where the statistical errors are no longer the limiting factors.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the β decay is populating a different set of lower-spin states than those populated by the heavy-ion reaction. For 43 Ar, four excited states were observed by Jelley et al using the 48 Ca(α, 9 Be) 43 Ar reaction [12], whereas Maréchal et al used inelastic proton scattering with a radioactive 43 Ar beam to identify a separate state [13]. Only the state at 1.74 ± 0.05 MeV has a possible corresponding state to those previously observed in β decay [8].…”
Section: Introductionmentioning
confidence: 99%